A tentative analysis of the causal stress factors of graduate students of the University of New Mexico in Albuquerque, New Mexico - Ledesma, Yolanda E.; Cobos, Angel R. (Maskana, 2016)
Stress reflects the body’s response to different demands, and it is generally accepted that good and bad experiences can cause stress. There is positive (eustress) and negative stress (distress), and both affect people. The factors causing stress range from physiological (e.g., fear of danger) too emotional (e.g., worry about money or family), and vary from person to person. The research question of this study was if the causes of stress are different between Latin American and American students at the Latin American Studies Program of the University of New Mexico (UNM) in Albuquerque, the United States. The article depicts how local and foreign graduate students perceive their stress. Findings revealed that the top four common stressors for college students are academic responsibility, time management, financial situation, and personal relationships. Six qualitative methods, such as observation, individual interviews, focus groups, collective analysis, social mapping, and visual analysis, were used to collect insight in the phenomenon of stress. The collected information was codified, organized, classified and consolidated using the Atlas.ti database, and analyzed using the triangulation technique. Results show that stress perception is significantly influenced by the cultural differences between the students.